FREQUENCY OF ANXIETY AND DEPRESSION AND ITS PSYCHOSOCIAL CORRELATES AMONG WOMEN RECEIVING ANTENATAL CARE IN A TERTIARY CARE HOSPITAL IN KARACHI - Rekhan, Rekhan; Ali Shah, Nighat; Tahir, Amber; Masood, Mehar; Fahim, Tanzila; Washdev, Washdev (Journal of Pakistan Psychiatric Society, 2024)
ObjectiveTo determine the proportion of women suffering from antenatal depression and anxiety visiting a tertiary care hospital for routine antenatal visits to evaluate the psychosocial factors associated with their depression and anxiety.Study DesignA descriptive cross-sectional studyPlace and DurationDepartment of Gynaecology & Obstetrics Ward 9B,   Jinnah Postgraduate Medical Center (JPMC), Karachi from January 2024 to May 2024.  MethodThis study was conducted with 249 pregnant women via non-probability, consecutive sampling. Anxiety and depression were assessed using Urdu validated version of Hospital Anxiety and Depression Scale. Psychosocial stressors were also recorded. Data was entered and analyzed using SPSS for Windows version 23.0.ResultsIn this study, 20% of women in their second and third trimesters of pregnancies were anxious and 5% were depressed. Critical psychosocial factors included low education, marital stressors such as low social support from husband and/or in-laws, living separately from husband, and intimate partner violence, financial stressors such as husband unemployment and pregnancy-related factors such as unplanned pregnancy and narrow birth spacing.ConclusionThe study provides a significant burden of antenatal mental health issues in our region and their specific associated psychosocial factors. The study emphasizes upon the need for Biopsychosocial support systems and interventions to mitigate the risk of antenatal depression and safeguard maternal well-being during this critical period.